PERAN KUALITAS LAYANAN DALAM MEMBANGUN KEPUASAN DAN KOMUNIKASI DARI MULUT KE MULUT PASIEN RAWAT JALAN RSD. DR. SOEBANDI JEMBER - Optimasi, Dini; Irawan, Bambang; Suroso, Imam (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
The purpose of this research is to analyze the effect of service quality on satisfaction and word-of-mouth communication, and the effect of satisfaction on word-of-mouth communication on the outpatients of the Regional Hospital of dr. Soebandi Jember. This is a quantitative research with an explanatory approach. The population is all outpatients of the Regional Hospital dr. Soebandi Jember. Applying purposive sampling method, the sample consists of 180 respondents. Data were analyzed by Structural Equation Modeling (SEM) method. The results show that service quality has no significant effect on satisfaction, service quality has no significant effect on word-of-mouth communication, and satisfaction has a significant effect on word-of-mouth communication. Keywords: Service Quality, Satisfaction, Word-of-Mouth Communication